Spominska retorika v literarni esejistiki Josepha Rotha - Birk, Matjaž (Primerjalna književnost, 2020)
The present discussion focuses on Juden auf Wanderschaft (1927), the central literary-essayistic work with a Jewish theme by the Jewish-Austrian writer and journalist Joseph Roth (1894-1939). Based on the theory of rhetoric of memory (A. Erll), it sheds light on narrative strategies and the correlation between the narrativization of collective memory and the literary representation of identities and cultural practices of Eastern European Jewry. Anchored in the flexible point between Western European and Eastern Jewish cultures, the author legitimizes cultural practices of Eastern European Jewry embedded between the spiritual and the sensory by connecting, in functional harmony with the monumental, the antagonistic and the experiential modes of the rhetoric of memory. In the prism of critical deconstruction of Western European ideological discourses, the discussion simultaneously reveals Jewish cultural self-deceptions, and, interweaving the antagonistic and the reflexive modes, sensitizes the reader for the perception of "the other status" and for the constructional character of culture. The shift of the barycenter of the rhetoric of memory from the contrastive to that of correspondence models humanity in the uber-ethical dimension, and exposes it as an ideational postulate for the attitude towards Eastern Jewry as a complementary foreignness (O. Schäffter). Despite cultural binarities as a product of antagonistic rhetoric of memory and irrespective of the historical pessimism relating to the fate of Jews, hybrid identity constructions offer the reader convincing signals for disclosing trans-differences and possibilities of ideational polyphony in intercultural communication.
Keywords: Austrian literature; avstrijska književnost; collective identity; collective memory; cultural polyphony; Eastern Europe; ideational polyphony; idejna polifonija; Judaism; judovstvo; kolektivna identiteta; kolektivni spomin; kulturna polifonija; literarna esejistika; literary essayism; Roth, Joseph; vzhodna Evropa